The Effect of Independence, Organizational Commitment and Digitalized Leadership Style on Auditor Performance in Public Accounting Firm in Bali Province - Yuliana Imelda Manu; Ni Made Galih Masari; I Ketut Merta; I Gusti Ayu Novita Sari (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to analyze the influence of independence, organizational commitment, and digital leadership style on auditor performance at Public Accounting Firms in Bali Province. Auditor performance is a crucial aspect in maintaining the credibility of financial statements and public trust in the accounting profession. Independence, organizational commitment, and the ability of leaders to adopt and implement a digital leadership style are believed to play a significant role in improving auditor performance in the current era of digital transformation. This research applies a quantitative approach with data collected through questionnaires distributed to auditors working at Public Accounting Firms in Bali Province. The sample was determined using a purposive sampling method, and the collected data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, the coefficient of determination (R²), and partial t-tests to examine the influence of each independent variable on auditor performance. The results show that (1) independence has a positive and significant effect on auditor performance, (2) organizational commitment has a positive and significant effect on auditor performance, and (3) digital leadership style also has a positive and significant effect on auditor performance. These findings emphasize that improving auditor performance can be achieved through strengthening independence, enhancing organizational commitment, and implementing a leadership style that is adaptive to digital developments